2006
DOI: 10.1111/j.1365-2893.2006.00797.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hepatitis B with lamivudine and tenofovir in HIV/HBV‐coinfected patients: factors associated with response

Abstract: As therapy for human immunodeficiency virus (HIV) infection evolves, optimizing hepatitis B virus (HBV) treatment and identifying factors that impact its response in the HIV/HBV-coinfected population is critical. We identified retrospectively 45 HBV/HIV-coinfected patients with detectable HBV DNA by the Bayer VERSANT HBV 3.0 bDNA assay (limit of quantification 2000 copies/mL) at baseline and/or year 1 of therapy. Patients were divided into three groups based on the active HBV agent in their antiretroviral regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
3
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 39 publications
3
49
3
1
Order By: Relevance
“…Also Jain et al demonstrate that infection with genotypes G, A/G, F and D is signifi cantly associated with non-response. 1,32,33 In contrast, Lacombe et al concluded in their study that baseline HBV genomics such as genotype did not infl uence HBV decay; similar results had been reported previously with LAM and ADV. 14,34,35 Stephan et al showed that patients with high-replicative virus may benefit from TDF therapy with a reduction in replicative status while subjects with low-level HBV replication who become undetectable HBV DNA and HBsAg carriers remain DNA negative.…”
contrasting
confidence: 46%
“…Also Jain et al demonstrate that infection with genotypes G, A/G, F and D is signifi cantly associated with non-response. 1,32,33 In contrast, Lacombe et al concluded in their study that baseline HBV genomics such as genotype did not infl uence HBV decay; similar results had been reported previously with LAM and ADV. 14,34,35 Stephan et al showed that patients with high-replicative virus may benefit from TDF therapy with a reduction in replicative status while subjects with low-level HBV replication who become undetectable HBV DNA and HBsAg carriers remain DNA negative.…”
contrasting
confidence: 46%
“…Resistance is rare and combination with 3TC or FTC has been demonstrated to be effective at suppressing HBV DNA and may induce HBeAg seroconversion. Combining 3TC/FTC with tenofovir may reduce the risk of breakthrough [137].…”
Section: Hiv Therapy Indicatedmentioning
confidence: 99%
“…If renal toxicity precludes the use of tenofovir, entecavir is an option that can be used along with a fully active antiretroviral regimen [137].…”
Section: Hiv Therapy Indicatedmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown to have an additive suppression effect on viral replication when administered in combination with lamivudine, entecavir or telbivudine [47,48] .…”
Section: Tenofovir Disoproxilmentioning
confidence: 99%